Therapy Effectiveness of Venous Leg Ulcer Treatment Methods - A Comparative Review - Gadziński, Patryk; Czechowicz, Marta; Madoń, Joanna (Journal of Education, Health and Sport, 2026)
Background Venous leg ulcers are a common health problem for patients suffering from chronic venous insufficiency. Despite the notable advances in prevention and treatment made during the past years, up to a third of VLUs still display significantly delayed or no healing, with an insufficient response to mainline therapy alone. Aim This literature review aims to showcase the available treatment methods of venous leg ulcers, their individual and, when possible, comparative effectiveness, as well as identify which patients would likely benefit from additional solutions and adjuncts, in order to improve healing outcomes and reduce recurrence. Materials and Methods This article reviews the existing literature on venous leg ulcer treatment. Original studies, reviews, and studies available in the Cochrane, PubMed, and Google Scholar databases were included. The literature review and article selection process concluded in November 2025. Results Data pooled from the available studies shows that compression therapy, paired with suitable lifestyle interventions, remains the backbone of venous leg ulcer treatment. Adjuncts such as pentoxifylline, wound dressings, and artificial skin grafts display a sufficiently well-established effectiveness in increasing healing effectiveness. The lack of high-quality studies comparing individual products and substances within each wider category largely limits the potential to formulate specific recommendations and should be viewed as a potential area for future research. Conclusions While the findings back up the effectiveness of the standard treatment for venous leg ulcers, consisting primarily of compression therapy, available adjuncts show potential to improve outcomes, particularly among patients with a high risk of delayed healing or those dealing with frequent recurrences, and should be considered when the appropriate indications are present.